Radical ecclesiology: The church as an arena for reconciliation through cultivating alternative community. Issue 1 (January 2020) - Hunter, Danny
Rising tensions in communities around the world have created contexts of conflict to which the church has been challenged to respond with a theology of reconciliation. This, however, raises the question: What kind of communities do we need in order to create such a theology amid so much conflict? Drawing on an Anabaptist vision of the church as an "alternative community, " this article demonstrates how dislocation amid conflict allows the church to become an arena for reconciliation by creating neutral social space, crafting new social narratives, and exercising creative freedom.